Increasing international tourism attractiveness of companies in Central Karelia with product development - Juvonen, Heta (Saimaan ammattikorkeakoulu, 2015)
The purpose of the thesis is to increase the attraction of the tourism companies with product development in the area of road 9 in Central Karelia. The thesis will find out the needs and resources of the businesses in product development. It also evaluates the core tourism products of the area which could be interesting from international tourists’ point of view. Finally it will give a few suggestions based on these findings on the possible tourism products that could be developed for the international tourists in the area. In other words the thesis attempts to give an idea of how the product development could work in the Central Karelian area. The information for this study was gathered from interviewing three case companies in Central Karelia in 2013 with a semi structured theme interview, literature, the Internet, newspapers and tourism brochures of the destination. The results show that tourism industry in Central Karelia is still to develop, and improvement concerning information flow is needed. The area has great tourism possibilities; however, cooperation between the companies and municipalities has to be increased in order to create more packages and improve the tourism attractiveness of Central Karelia. Perhaps a company that would specialize in creating and selling tourism packages for international tourists is an opportunity to facilitate the product development process.